Rainfall orientated management for a multiherbivore grazing system - Berry, Mark Philip Seager (My University, 2016)
This dissertation investigated vegetation-herbivore interactions and formulated a strategy for managing multiherbivore systems under varying rainfall regimes. [Abbreviated Abstract. Open document to view full version]
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, for the Degree of Doctor of Philosophy